Dilema Penggunaan “Syariah” Dalam Deklarasi-Deklarasi HAM Islam - Hudin, Nurul Amin (Living Islam: Journal of Islamic Discourses, 2019)
Among the many religions in the world, Islam is the only religion that explicitly declares the notion of human rights known as al-Bayàn al-`Alam ‘an Huqùq al-Insàn fi al-Islàm (Universal Declaration of Human Rights in Islam). Therefore, it is clear that Islam truly respects human rights. However, the use of the term "Islam" in the declaration implies that the declaration was based on sharia. Even though the principles of sharia in question tend to discriminate against other religious groups, slaves, and women. This article will explain some of the ambiguities in the Universal Declaration of Human Rights in Islam and suggest more adequate ideas in the enforcement of human rights campaigns in the Islamic world.